FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR PAJAK (Studi Pada UKM di Kota Semarang) - Ita Purnawati, 13.05.52.0151; Meita Oktaviani, Rachmawati (Students' Journal of Accounting and Banking, 2017)
This research aims to analyze the factors that affect individual taxpayers in meeting their to pay taxes obligations. This research consists of four independent variables and one dependent variables. Independent variables in this research is the knowledge and understanding of taxation, perception of the tax system, quality of service a fiscus, and awareness a taxpayer. While the dependent variables in this research is the willingness to pay taxes.This research uses convinience sampling technique a number of 83 respondents. Respondents of were sampled in this study is an individual taxpayer who have business and registered in the Ministry of Cooperatives and SMEs Semarang City. Analysis of research data using multiple linear analysis with SPSS 17.0 program.Based on the results of the analysis has been done, this research show that awareness a taxpayer and knowledge & understanding of taxation have not significant effect toward willingness to pay taxes. Quality of service a fiscus and a good perception of the tax system have a significant of positive effect toward willingness to pay taxes.Keywords: Knowledge and Understanding of Taxation, Perception of The Tax System, Quality of Service a Fiscus, Awareness a Taxpayer, Willingness to Pay Taxes